Perancangan Sistem Two-Factor Authentication (2FA) Pada Aplikasi E-Commerce - Daffa Sholah Islamey; Joko Sutopo (Jurnal Indonesia Sosial Teknologi, 2025)
The development of digital technology has given significant changes to human life, especially in the Internet world, the Internet makes it easier for humans to carry out daily activities and work. However, this convenience can also increase the threat of cybercrime. This research aims to implement a security system based on Two-Factor Authentication (2FA) with a One-Time Password (OTP) on Android applications, to protect data from cybercrimes such as Phishing data theft and ransomware. The research method used is the waterfall model, which contains system analysis discussing what is needed in building applications with 2FA and OTP security, system design discusses the system flow that will be applied and created, coding discusses how the backend can run the system flow created, and implementation discusses the application of previous results. The result of the research obtained is that the implementation of Two-Factor Authentication (2FA) using a One-Time Password (OTP) can improve the security of user data by providing an additional layer of security that reduces unauthorized access rights, this also provides a safer experience for application users who implement it.